TANGGUNGJAWAB SOSIAL PERUSAHAAN DAN TINGKAT KEBERDAYAAN EKONOMI RUMAH TANGGA - Sumaryo, Sumaryo (Universitas Muhammdaiyah Surakarta, 2011)
The objectives of the study are: (1) to identify the influence of CSR implementation toward the community behavior progress on their business, (2) to identify the influence of CSR implementation to the household economic capability, and (3) to formulate and to design strategy to improve the community business capability and their income. LISREL was used to formulate the Structural Equation Modelling of CSR implementation. The important results show: (1) facilitatorsâ competency and supporting factors are significantly influence to the community business capability, while individual characters and quality program do not significantly influence to the community business capability, (2) the community business capability does significantly influence to the level of houseold economic capability, (3) the âparticipative CSRâ is recomemmeded as a model of CSR implementation.